Creation of MOPOKAR (Card Monopoly) to Enhance Learning Skills in Comparing the Social Conditions of Indonesia and Neighboring Countries in Grade 6 - Dirgantara, Cahya Sukma; Hanifah, Nurdinah; Nugraha, Dadan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to create MPOKAR-based (Monopoly Card) learning media and determine its effectiveness in improving students' learning skills. The research employs the Research & Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques include observation, questionnaires, and tests. The study population consists of sixth-grade students in SDN Pakubeureum 1, located in the Kertajati sub-district of Majalengka Regency, West Java. Random sampling is used to select ten respondents for the study. The collected data are then descriptively analyzed using the SPSS program. The resulting media is highly valid, with a material percentage of 82.5% and a media aspect percentage of 98%. The media's feasibility test yields a percentage of 95%, categorized as highly feasible. Subsequently, the test results (pre-test and post-test) using the one-group pretest-posttest design on ten sixth-grade students show an average pre-test score of 54.00 and a post-test score of 82.00. It is concluded that the post-test results are greater than the pre-test, indicating an improvement in students' learning outcomes. Based on the research findings, it can be stated that the MOPOKAR ASEAN (Monopoly Card) media can enhance learning skills and is thus deemed suitable for use as a learning tool in elementary schools.